2005
DOI: 10.1021/es0505503
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Lubricant on the Formation of Heavy-Duty Diesel Exhaust Nanoparticles

Abstract: The effect of lubricants on nanoparticle formation in heavy-duty diesel exhaust with and without a continuously regenerating diesel particulate filter (CRDPF) is studied. A partial flow sampling system with a particle size distribution measurement starting from 3 nm, approximately, is used. Tests are conducted using four different lubricant formulations, a very low sulfur content fuel, and four steady-state driving modes. A well-documented test procedure was followed for each test. Two different kinds of nanop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
103
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
2
1

Relationship

3
7

Authors

Journals

citations
Cited by 112 publications
(107 citation statements)
references
References 27 publications
4
103
0
Order By: Relevance
“…A similar sampling system has been used in several vehicle or engine exhaust studies. 14,15,28 Particle size distributions were measured with a filter stage-equipped electrical low-pressure impactor (ELPI; Dekati, Ltd. 29,30 ) and with two scanning mobility particle sizers (SMPS). 31 The measurement range of ELPI was from 7 nm to 6.6 m. The ELPI was used to observe the stability of the measured particle size distribution.…”
Section: Size Distribution Measurementsmentioning
confidence: 99%
“…A similar sampling system has been used in several vehicle or engine exhaust studies. 14,15,28 Particle size distributions were measured with a filter stage-equipped electrical low-pressure impactor (ELPI; Dekati, Ltd. 29,30 ) and with two scanning mobility particle sizers (SMPS). 31 The measurement range of ELPI was from 7 nm to 6.6 m. The ELPI was used to observe the stability of the measured particle size distribution.…”
Section: Size Distribution Measurementsmentioning
confidence: 99%
“…Vaaraslahti et al 29,30 investigated in the laboratory the effect of lubricating oils on emissions from a heavyduty diesel engine with and without a continuously regenerating diesel particulate filter (CRDPF). Four types of oils were used with sulfur content varying from 1600 to 9330 parts per million (ppm).…”
Section: ϫ3mentioning
confidence: 99%
“…Owing to their small size and complicated chemical and physical characteristics (3)(4)(5)(6), atmospheric particles resulting from traffic emissions pose a significant risk to human health (7)(8)(9)(10)(11)(12), and also contribute to anthropogenic forcing of climate (13,14). Previous research on vehicular emissions has demonstrated the presence of soot and ash (3,15) and solid sub-10-nm core particles (4)(5)(6) in primary emissions from vehicles and engines and their variation, depending on vehicle technologies (4,6), the properties of fuels and lubricant oils (15,16), and driving conditions (15)(16)(17). In addition to particles, exhaust typically contains species that reside in the gaseous phase in the undiluted high-temperature exhaust (5,18,19) but condense or even nucleate to the particle phase immediately after the exhaust is released to the atmosphere.…”
mentioning
confidence: 99%